The rules of engagement: physician engagement strategies in intergroup contexts. Issue 1 (11th March 2014) - A. Kreindler, Sara; K. Larson, Bridget; M. Wu, Frances; N. Gbemudu, Josette; L. Carluzzo, Kathleen; Struthers, Ashley; D. Van Citters, Aricca; M. Shortell, Stephen; C. Nelson, Eugene; S. Fisher, Elliott
Abstract : Purpose: – Recognition of the importance and difficulty of engaging physicians in organisational change has sparked an explosion of literature. The social identity approach, by considering engagement in terms of underlying group identifications and intergroup dynamics, may provide a framework for choosing among the plethora of proposed engagement techniques. This paper seeks to address this issue. Design/methodology/approach: – The authors examined how four disparate organisations engaged physicians in change. Qualitative methods included interviews (109 managers and physicians), observation, and document review. Findings: – Beyond a universal focus on relationship-building, sites differed radically in their preferred strategies. Each emphasised or downplayed professional and/or organisational identity as befit the existing level of inter-group closeness between physicians and managers: an independent practice association sought to enhance members' identity as independent physicians; a hospital, engaging community physicians suspicious of integration, stressed collaboration among separate, equal partners; a developing integrated-delivery system promoted alignment among diverse groups by balancing "systemness" with subgroup uniqueness; a medical group established a strong common identity among employed physicians, but practised pragmatic co-operation with its affiliates. Research limitations/implications: – The authors cannot confirm the accuracy of managers' perceptions of the inter-group context or the efficacy of particular strategies. Nonetheless, the findings suggested the fruitfulness of social identity thinking in approaching physician engagement. Practical implications: – Attention to inter-group dynamics may help organisations engage physicians more effectively. Originality/value: – This study illuminates and explains variation in the way different organisations engage physicians, and offers a theoretical basis for selecting engagement strategies.